2017
DOI: 10.1093/biolre/iox146
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone, the maternal immune system and the onset of parturition in the mouse†

Abstract: The role of progesterone (P4) in the regulation of the local (uterine) and systemic innate immune system, myometrial expression of connexin 43 (Cx-43) and cyclooxygenase 2 (COX-2), and the onset of parturition was examined in (i) naïve mice delivering at term; (ii) E16 mice treated with RU486 (P4-antagonist) to induce preterm parturition; and (iii) in mice treated with P4 to prevent term parturition. In naïve mice, myometrial neutrophil and monocyte numbers peaked at E18 and declined with the onset of parturit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 53 publications
(71 reference statements)
3
26
0
1
Order By: Relevance
“…The total number of circulating natural killer cells and secretion of pro-inflammatory cytokines (IFN-gamma) is also reduced in the pregnant state (Veenstra Van Nieuwenhoven et al, 2002 ). However, close to parturition, the maternal immune system shifts to a pro-inflammatory state, particularly locally within the uterus, to promote labor (Mor and Cardenas, 2010 ; Edey et al, 2018 ). There are also specific changes in the numbers of different leukocyte populations in the maternal thymus and spleen during pregnancy (Clarke and Kendall, 1994 ; Kendall and Clarke, 2000 ; Norton et al, 2009 ).…”
Section: Adaptations In Maternal Physiology During Pregnancy and Lactmentioning
confidence: 99%
“…The total number of circulating natural killer cells and secretion of pro-inflammatory cytokines (IFN-gamma) is also reduced in the pregnant state (Veenstra Van Nieuwenhoven et al, 2002 ). However, close to parturition, the maternal immune system shifts to a pro-inflammatory state, particularly locally within the uterus, to promote labor (Mor and Cardenas, 2010 ; Edey et al, 2018 ). There are also specific changes in the numbers of different leukocyte populations in the maternal thymus and spleen during pregnancy (Clarke and Kendall, 1994 ; Kendall and Clarke, 2000 ; Norton et al, 2009 ).…”
Section: Adaptations In Maternal Physiology During Pregnancy and Lactmentioning
confidence: 99%
“…22 Simvastatin has previously been shown by our group to minimize infection-associated inflammation. 36,37 Progesterone is a vital hormone for the continuum of pregnancy. 30 It has been studied in various inflammatory conditions such as rheumatoid arthritis, 31 asthma, 32 and stroke 33 where it has shown to reduce the expression of proinflammatory cytokines and chemokines.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Similarly, progesterone is a well-reported anti-inflammatory agent. 36,37 Progesterone is a vital hormone for the continuum of pregnancy. 38 Although not successful, both 17-hydroxy progesterone caproate and vaginal administration of progesterone have been used extensively in an attempt to minimize the risk of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that activation of the p38 MAPK pathway by oxidative stress in human fetal membrane tissues causes cellular senescence and sterile inflammation, which are postulated to trigger parturition . Animal model studies have also confirmed its potential role in the initiation of labor . However, it is premature to state that p38 MAPK is the key mediator of parturition based on its activation in chorioamniotic membranes to various stimuli.…”
Section: Introductionmentioning
confidence: 99%